Status Gizi dan Perilaku Sehat pada Remaja - Rahmawati, Helfi; Fatmawati, Tina Yuli; Efni, Nel (3031-8572, 2023)
PHBS is an activity to empower students, teachers and the community in the school environment to want to implement and practice PHBS patterns in order to create a clean and healthy school environment. The purpose of this study was to find out the description of nutrition status and clean and healthy living behavior (PHBS) of students at SMP Negeri 8 Jambi city. This type of research is descriptive research which aims to find out the description of PHBS in adolescents at SMPN 8 Jambi City. Data collection was carried out on adolescents at SMPN 8 Jambi City from November to July 2023. The population in this study were all students of SMPN 8 Jambi City totaling 653 people. This study used a simple random sampling technique with a total of 63 students. Furthermore, the data were analyzed in the form of univariate analysis. The results of the study can be concluded that the age distribution of the respondents was mostly at the age of 14, the majority were female, the majority have a poor nutritional status, and the healthy behavior of the respondents was not good. It is recommended that teenagers should always look for good information through print/electronic media about PHBS, teenagers are advised to apply PHBS in their daily activities so they can avoid various kinds of diseases